Efficacy of DHEA to fight against ovarian ageing - Narkwichean, Amarin (2018)
There is an increase in the number of women with subfertility, who seek assisted reproductive technology (ART) treatment to overcome involuntary childlessness due to ovarian ageing, but which is commonly associated with poor response to ovarian stimulation protocols resulting in poor outcomes during ART. A few clinical studies have shown that DHEA, an androgen mainly secreted from the adrenal glands, can improve ovarian response and increase the chances of pregnancy after in vitro fertilisation (IVF) treatment in women affected by ovarian ageing. However, clinical evidence as well as knowledge regarding underlying mechanisms of DHEA on improving ovarian response is still limited.